Interleukin-7 Induces Osteoclast Formation via STAT5, Independent of Receptor Activator of NF-kappaB Ligand - Kim, Jin-Hee; Sim, Ji Hyun; Lee, Sunkyung; Seol, Min A.; Ye, Sang-Kyu; Shin, Hyun Mu; Lee, Eun Bong; Lee, Yun Jong; Choi, Yun Jung; Yoo, Wan-Hee; Kim, Jin Hyun; Kim, Wan-Uk; et al. (Frontiers in Immunology, 2017)
Interleukin-7 (IL-7), which is required for the development and survival of T cells in the thymus and periphery, plays a role in joint destruction. However, it remains unclear how IL-7 affects osteoclast formation. Thus, we investigated the mechanism by which IL-7 induced osteoclast formation through IL-7 receptor α (IL-7Rα) in osteoclast precursors. We cultured peripheral blood mononuclear cells or synovial fluid mononuclear cells with IL-7 in the presence or absence of an appropriate inhibitor to analyze osteoclast formation. We also constructed IL-7Rα-expressing RAW264.7 cells to uncover the mechanism(s) by which IL-7 induced osteoclast formation differed from that of receptor activator of nuclear factor B ligand (RANKL). We found that IL-7 induced osteoclast formation of human monocytes from peripheral blood or synovial fluid in a RANKL-independent and a signal transducer and activator of transcription 5 (STAT5)-dependent manner. IL-7-induced osteoclasts had unique characteristics, such as small, multinucleated tartrate-resistant acid phosphatase positive cells and no alterations even when RANKL was added after IL-7 pretreatment. RAW264.7 cells, if overexpressing IL-7Rα, also were able to differentiate into osteoclasts by IL-7 through a STAT5 signaling pathway. Furthermore, IL-7-induced osteoclast formation was repressed by inhibitors of the IL-7R signaling molecules Janus kinase and STAT5. Our findings demonstrate that IL-7 is a truly osteoclastogenic factor, which may induce osteoclast formation via activation of STAT5, independent of RANKL. We also suggest the possibility that an IL-7R pathway blocker could alleviate joint damage by inhibiting osteoclast formation, especially in inflammatory conditions.